The Influence of Using the Project Based Learning (PjBL) Method on Students' Creative Thinking Skills in the Subject of Akidah Akhlak - Adrianto Satingi; Razak H. Umar; Mariaty Podungge; Nurul Lutfiah Nusi (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the effect of the Project Based Learning (PjBL) method on students’ creative thinking skills in the subject of Akidah Akhlak at MTs Negeri 1 Bolaang Mongondow Selatan. This research employed a quantitative approach with a pre-experimental design using a one group pretest-posttest design. The sample consisted of 21 seventh-grade students selected based on the suitability of the class and learning material. Data were collected through a creative thinking skills questionnaire, documentation, and project assessment. The instrument measured four indicators of creative thinking, namely fluency, flexibility, originality, and elaboration. The reliability test showed a Cronbach’s Alpha value of 0.823, indicating that the instrument was reliable. The Shapiro-Wilk normality test showed that both pretest and posttest data were normally distributed, with significance values of 0.784 and 0.478, respectively. The results revealed that the mean pretest score of 53.4286 increased to 63.8095 in the posttest. The Paired Sample t-Test obtained a t value of -5.249 with a significance value of 0.000 < 0.05. Therefore, the use of the Project Based Learning method had a significant effect on improving students’ creative thinking skills in Akidah Akhlak learning.